Network quality and user perception improvement of high-speed rail scene - Songbai LIANG; Yingwu GUO; Xinwei LI (Dianxin kexue)
In view of the difficulty in improving the quality of mobile network in high-speed railway scenes and the poor efficiency of conventional methods, a methodology system for improving the perception of mobile communication users was explored in traffic trunk lines, especially in high-speed railway scenes.The methodology system was based on handover chain optimization with the core idea of “primary covering, reasonable reselection and orderly switching”.It adopted a three-layer theoretical structure include covering control firstly, then parameter optimization, and feature loading last.It used idle state and service state data pull graph correlation to determine problem road sections and cells, match the delay parameters of high-speed mobile scenes, load service quality and perception characteristics, and greatly improved the high-speed railway network quality and user perception.This method started from the principle analysis, with practical application, it could effectively solve the network problems, which could be fully extended to other linear scenes.